Risk assessment of herbal supplements containing ingredients that are genotoxic and carcinogenic. (9th August 2019) - Prinsloo, Gerhard; Steffens, Francois; Vervoort, Jacques; Rietjens, Ivonne M.C.M.
Abstract: Botanicals and botanical preparations including plant food supplements as well as medicinal herbal supplements can contain possible beneficial health compounds, but also ingredients of concern. Compounds that are both genotoxic and carcinogenic have been found in herbal supplements and may raise a safety concern. Genotoxic carcinogens that can be present in botanicals and botanical preprations include especially pyrrolizidine alkaloids (PAs), aristolochic acids (AAs) and alkenylbenzenes (ABs). The present manuscript provides an overview of the levels of these compounds reported to date to be present in herbal supplements with an associated risk assessment. Exposure was estimated based on levels of PAs, AAs and ABs in individual supplements and their proposed uses. In addition a probabilistic exposure assessment was performed based on the distribution of the level of the compounds of concern in the food supplements and of the recommended uses, resulting in 5th to 95th percentile consumer exposure values. To evaluate the risk of these exposures, the margin of exposure (MOE) approach for lifetime exposure was used. To correct exposure estimates for shorter than lifetime exposure, Haber's rule as a first tier approach was applied. It is concluded that the proposed uses and use levels as well as the presence of AAs, ABs and PAs in food supplements should be carefully monitored to manage potential consumer risks. More information on estimated daily intake resulting from supplement use, as well as consequences of concomitant exposure will further improve the risk evaluation of products containing these compounds of concern.